(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article considers the issue of “informational society”, in which communication is the basis for the activities of political scientists, sociologists, philologists, culturologists, psychologists, historians and cyberneticians and other scientists who have devoted their research to the issue of humanities disciplines. The possibility of reflexion prompts the author to refer to them as disciplines within the zone of influence of communicativism. Therefore, there is nothing surprising, for example, in the emergence of the concept of “information society”, which arises only on the basis of the intersection of the two original concepts - society and information.